Quality of life and complications in lower limb amputees in Tanzania: results from a pilot study. (March 2018) - Shaw, Jeremy; Challa, Sravya; Conway, Devin; Liu, Max; Haonga, Billy; Eliezer, Edmund; Morshed, Saam; Shearer, David
Abstract: Background: The most common reason for lower extremity amputation in developing countries is trauma, which is an increasingly recognised global epidemic. Despite the rising rates of traumatic injury and the level of disability experienced by amputees, there are few data focusing on this specific population in low-income and middle-income countries (LMICs). The purpose of this study is to investigate the causes and health-related outcomes of lower extremity amputations in Tanzania, and the socioeconomic barriers preventing access to prosthetics. Methods: This was an observational pilot study conducted at the Muhimbili Orthopaedic Institute in Dar es Salaam, Tanzania, from 2015 to 2016. Adult patients who had undergone lower extremity amputation less than 1 year before enrolment were included. Baseline data on demographics, socioeconomic factors, and health-related information were collected at enrolment. Patients' health, health-related quality of life (using the EQ-5D questionnaire), and complication data were recorded 3 and 6 months later. Findings: We enrolled 44 patients, 35 of whom were men, with a mean age of 39·5 years. 39 (89%) of the patients were employed (36 [82%] informally) and 36 (82%) had no health insurance. Below-knee amputations were the most common (23 [52%]) type of amputation. The most common cause of amputation was trauma (29 [66%]), followed by diabetes (7 [16%]), vascular pathology (3 [7%]), and tumours (2 [5%]). Complications including delayed healing, infection, and wound dehiscence were seen in 20 (51%) of the 39 patients who were followed up. Seven patients required reoperation. The average baseline EQ-5D index was 0·912. The population norm based on mean age is 0·889 for the USA and 0·793 for Zimbabwe (the only African country-specific norm available). The average EQ5D index at 3 months and 6 months decreased to 0·714 and 0·847, respectively. Only two amputees (5%) have received a prosthetic. Lack of materials, unsuitable wound, and cost were most commonly cited as barriers to prosthetics. Interpretation: This study demonstrates that amputees in Tanzania experience a high rate of post-operative complications, poor quality of life, and extremely limited access to prosthetics. Educational initiatives to reduce wound-related complications and improved access to lower extremity prosthetics and rehabilitation are needed to address the dearth of knowledge and resources for amputees. Funding: Global Research Initiative.